Pengujian Mesin Peniris Minyak Goreng Keripik Kentang Kapasitas 20 kg - Zulfani, M; Hermanto, Tino; Nasution, Arya Rudi (CV. IRA PUBLISHING, 2025)
This study aims to analyze the performance of oil slicing machines on potato chip products that are specifically designed for the needs of small-scale food industries. The machine has a capacity of 10 kg and is operated for 3 minutes per cycle. The test was conducted five times on potato chip samples, with the primary parameters being the weight before and after the slicing process. The average weight of chips before draining is 568 grams, while after draining, it decreases to 529 grams, indicating a 39-gram decrease in mass, which corresponds to a reduction in oil content. The calculation of the thinning efficiency revealed that the engine was capable of reducing the oil content by up to 6.87% of the initial weight. The engine is driven by an electric motor with a rotation of 1380 rpm, transmitted through a pulley system (3 inches: 13 inches), resulting in a tube rotation of 330.5 rpm. These results demonstrate that the slicing machine effectively reduces the oil content of potato chips in a short time, making it suitable for micro and small businesses in the snack sector due to its simplicity, energy efficiency, and cost-effectiveness.